2012
DOI: 10.5588/ijtld.10.0762
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode with various sputum smear preparation techniques to diagnose tuberculosis

Abstract: S E T T I N G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In line with previous studies we found that LED-FM had a higher sensitivity, but a lower specificity compared to ZN-microscopy [11], [21]. By using the new definition of a positive smear (≥1 AFB/length) from WHO [8], LED-FM in our study showed a relatively low specificity, resulting in a significant number of false-positive results based on ‘scanty smears’.…”
Section: Discussionsupporting
confidence: 88%
“…In line with previous studies we found that LED-FM had a higher sensitivity, but a lower specificity compared to ZN-microscopy [11], [21]. By using the new definition of a positive smear (≥1 AFB/length) from WHO [8], LED-FM in our study showed a relatively low specificity, resulting in a significant number of false-positive results based on ‘scanty smears’.…”
Section: Discussionsupporting
confidence: 88%
“…5 Previous studies have demonstrated that concentration of sputum by various methods signifi cantly increases the yield of PTB cases by conventional light and light-emitting diode fl uorescence microscopy (LED-FM). 6,7 Most studies used varying chemical methods and sedimentation methods, were based on a small sample, or were conducted at specialised centres. 7 While studies on optimising microscopy have been performed in reference laboratories, no studies have been reported under routine programme conditions in I ndia.…”
Section: Vol 3 No 1 Published 21 March 2013mentioning
confidence: 99%
“…This helps avoid delay in diagnosis and subsequent initiation of treatment, thus preventing further spread of the disease. 8 The study intended was to determine the diag-nostic accuracy of LED-FM and conventional ZN stain-ing taking Mycobacterial tuberculosis culture as the "Gold Standard" for resource-poor settings.…”
Section: Introductionmentioning
confidence: 99%